2022
DOI: 10.1155/2022/3475897
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis on the Social Environment of College Students’ Rural Employment and Entrepreneurship

Abstract: This paper aims to further solve the risks encountered by college students in the process of employment and entrepreneurship in rural areas and improve the success rate of employment and entrepreneurship. It presents a method of social environment analysis based on college students’ rural employment and entrepreneurship. This method deeply understands the employment and entrepreneurship environment of college students, deeply analyzes and identifies the constituent elements of college students’ rural employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…16 ItÕs increasingly common for students to browse the internet and social media platforms as they consider career paths. 27 This study collected data using just one image search engine. But if our key findingsÑ the limited inclusion of darker skin tones in images across roles, and the gender bias behind showing most students and nurses as female and most physicians as maleÑare any indication of what might be found via other search engines and social media platforms, many potential students and qualified job seekers wonÕt see themselves represented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 ItÕs increasingly common for students to browse the internet and social media platforms as they consider career paths. 27 This study collected data using just one image search engine. But if our key findingsÑ the limited inclusion of darker skin tones in images across roles, and the gender bias behind showing most students and nurses as female and most physicians as maleÑare any indication of what might be found via other search engines and social media platforms, many potential students and qualified job seekers wonÕt see themselves represented.…”
Section: Discussionmentioning
confidence: 99%
“…It's increasingly common for students to browse the internet and social media platforms as they consider career paths 27. This study collected data using just one image search engine.…”
Section: Discussionmentioning
confidence: 99%
“…For college students upon graduation, the career choice is a big choice to make. If they cannot master the effective job information or well prepare themselves for employment, then they would face a muddy choice when determining their career direction in the future [1][2][3][4][5][6][7][8][9][10][11][12]. At this time, the occupational values are playing a significant role in instructing the career decisions of college students who do not have a clear career goal, especially in aspects of career expectation, career selection, job search, job training, and job satisfaction [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%